Biomedical Dietetic Study: The Relationship of Body Mass Index and Total Cholesterol Levels with Blood Pressure Among Workers in Indralaya, Indonesia - Nur Sidiq, Ahmad; Ardila, Devi; Sripratiwi, Chesy; Paizer, Dindi (Yayasan Rumah Ilmu Professor, 2025)
Body Mass Index (BMI), total cholesterol levels, and blood pressure are important indicators in evaluating metabolic health status. These factors are interconnected and collectively influence the increased risk of cardiovascular diseases. This study analyzed the relationship between BMI, total cholesterol levels, and blood pressure among workers in Indralaya, Indonesia. Using a cross-sectional design, the study involved 30 purposively selected respondents. Data were collected through interviews, measurements of height and weight, total cholesterol examination, and blood pressure assessment. Data analysis was performed using Pearson correlation and linear regression. The results indicated a tendency for an association between BMI and blood pressure, although not statistically significant. Total cholesterol levels were not significantly associated with blood pressure. Regression analysis revealed that BMI contributed more strongly than blood pressure values. From a biomedical dietetic perspective, obesity has the potential to increase the risk of hypertension and dyslipidemia through mechanisms involving inflammation, insulin resistance, and atherosclerosis. Dietary interventions, such as balanced nutrition, limitation of saturated fats, and increased fiber intake, are recommended to reduce cardiometabolic risks.